Pengaruh Anggaran Berbasis Kinerja, Sistem Akuntansi Keuangan Daerah, Sistem Informasi Pengelolaan Keuangan Daerah Terhadap Penilaian Kinerja Satuan Kerja Perangkat Daerah (Studi Kasus Pemerintah Daerah Kota Surakarta) - Septyanto, Hendy; , Dra.Mujiyati M,Si (2015)
This study aimed to examine the effect of performance-based budgeting, the financial accounting system and financial management information systems on performance appraisal work unit area in Surakarta. The data in this study were collected by using a survey method with the help of a questionnaire research instruments totaling 70 pieces were distributed directly to 25 working units that exist in the upstream Surakarta addressed directly to the chief financial officer, treasurer, and staff compiler financial statements work on the local work force. The data in this study will be analyzed using multiple linear regression with the help of SPSS software version 17.0. To test the validity and reliability of research instrument used Pearson correlation and Cronvach Alpha. Besides, it is also done testing data normalization using a normal probability plot. The results of this study indicate that the performance-based budgeting, the financial accounting system, financial management information systems and a significant positive effect on performance appraisal work unit area.The amount Adjusted R2 Performance-based budgeting, the financial accounting system, financial management information systems area, performance assessment work unit area is 50.2%. While the remaining 49,8% is influenced by other variables that are not described in this study